2017
DOI: 10.1158/2326-6066.cir-16-0194
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Peptide Vaccines to Induce Robust Antitumor CD4 T-cell Responses

Abstract: Substantial evidence indicates that immunotherapy is a feasible and effective approach for the treatment of numerous types of cancer. Among various immunotherapy options, peptide vaccines to generate antitumor T cells appear as promising candidates, because of their cost effectiveness and ease of implementation. Nevertheless, most peptide vaccines are notorious for being weekly immunogenic and, thus, optimization of the vaccination strategy is essential to achieve therapeutic effectiveness. In addition, effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 52 publications
(74 reference statements)
1
48
0
Order By: Relevance
“…Murine studies show that T CD4 are required for induction of CD8 antitumor T cell responses [2,3]. Recent very comprehensive analysis of cellular subsets in cancer immunity highlight the crucial role of proliferating, activated effector memory Th1 T CD4 (CD69 + T-bet + CD44 + CD62L neg CD27 low CD90 hi ) in effective antitumor immunity [4] and showed that T CD4 induce more durable immune-mediated tumor control than T CD8 .…”
Section: Key Roles Of Tcd4 Lymphocytes In Anti-tumor Immune Responsesmentioning
confidence: 99%
“…Murine studies show that T CD4 are required for induction of CD8 antitumor T cell responses [2,3]. Recent very comprehensive analysis of cellular subsets in cancer immunity highlight the crucial role of proliferating, activated effector memory Th1 T CD4 (CD69 + T-bet + CD44 + CD62L neg CD27 low CD90 hi ) in effective antitumor immunity [4] and showed that T CD4 induce more durable immune-mediated tumor control than T CD8 .…”
Section: Key Roles Of Tcd4 Lymphocytes In Anti-tumor Immune Responsesmentioning
confidence: 99%
“…The most significant issue for selecting a TAg is related to potential immune tolerance that could affect the quality of the T cell response (capacity to recognize the tumor cell). Nevertheless, there are examples of successfully eliciting anti-tumor T cell responses to “self-antigens”, when immune tolerance was predicted [1821]. …”
Section: Antigen Selectionmentioning
confidence: 99%
“…Many of these peptides function as promiscuous epitopes (can be presented by several MHC-II alleles), potentially allowing their use as vaccines in broad patient populations. Following the model used with CTL vaccines, we reported the use of TriVax for eliciting substantive HTL responses in mice [21]. As with CTLs, the induction of HTLs by TriVax required a systemic prime-boost peptide administration and relied on IFN-I.…”
Section: Optimization Of Peptide Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the absence of co-stimulating PRR [19] or TCR [20], or stimulation prior to T cell receptor engagement ([••21]; our unpublished data), CD40 stimulation can have deleterious effects on CD8 + T cell responses. Conversely, the combination of TLR stimulation and CD40 stimulation has become the gold-standard in protein-based cancer vaccines in pre-clinical models, often generating a response where 20–40% of the CD8 + T cells in the immunized animal being specific for the vaccinating antigen, and targeting CD40/TLR in combination with vaccination has been successful in control established tumors in multiple mouse [11;22;••23]. In these studies, and in our experience, vaccination with anti-CD40 and peptide in the context of a TLR agonist is sufficient to drive large CD8+ T cell populations into tumors that were hitherto poorly infiltrated with T cells.…”
Section: Initiating the Cd8+ T Cell Responsementioning
confidence: 99%